STRATEGI PEMUNGUTAN PBB SEBAGAI UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH DI KOTA MOJOKERTO - Donovan, Deny; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the strategy which has been used by the municipal government of Mojokerto city incollecting PBB-P2, to find out the efficiency and the effectiveness level of the collection of PBB-P2, to find out the growth rateof land and building tax receipts to the local own-source revenue of Mojokerto city. This research is qualitative descriptiveresearch which is done by using the data collection techniques, i.e.: observation, interview, documentation and themeasurement of performance is carried out by using value for money method. The result of the research shows that themunicipal government of Mojokerto city has run the collecting strategy of PBB-P2 i.e.the acceleration oflegalinstitutionproviders, the provision ofmodern tax administration system, in cooperationwithother government agencies,conductingtechnical guidanceto the tax collector officers, provideonlinepayments, public coaching, provide mobile serviceDPPKA car, the implementation ofrewardsand punishment system, andestablish arole modelweek.The analysis of therealization of the local government budget in 2013-2014 periods explains that the level of efficiency in 2014 is 22.09% is notas efficient as in 2013 which is 19.75% which indicates the enhancement of the level of expenditures in 2014 has not beenable to generate maximum revenue realization compare to the previous year which has made the decline of contribution ofland and building tax to the local own-source revenue (PAD) of Mojokerto city from 7.30% in 2013 becomes 5.55% in 2014.Overall the collection of PBB-P2 has met with the achievement of the realization of revenue target but it has not optimal yetin improving the contribution of the local own-source revenue (PAD) of Mojokerto city.Keywords: Land and Building Tax, Land and Building Tax Collection Strategy, Value for Money.